Exchange rates under the East Asian dollar standard : living with conflicted virtue - McKinnon, Ronald I. (MIT Press, 2005)
The increasingly integrated economies of East Asia--China, Hong Kong, Indonesia, Japan, Korea, Malaysia, the Philippines, Singapore, Taiwan, and Thailand--face the dilemma of how to achieve exchange-rate security in the absence of a unifying "Asian euro." The US dollar has become the region's dominant intraregional trading currency as well as the monetary anchor to which East Asian economies informally peg their currencies. In this timely and original analysis of the benefits and risks of an East Asian dollar standard, Ronald McKinnon takes issue with the conventional view that urges flexible exchange rates on financially fragile economies. He argues instead that East Asian countries should coordinate their policies to keep their exchange rates stable against the dollar. McKinnon develops a conceptual framework to show where the conventional wisdom on exchange rates has gone wrong. Pressure on the "virtuous" high-saving dollar-creditor East Asian nations to appreciate their currencies leads to a "conflicted" choice between a possible deflationary slump if they do appreciate and threatened trade sanctions if they do not. Analyzing interactions among the East Asian economies, McKinnon explains the rationale, and the need, for greater exchange-rate security in the region, pointing to the soft-dollar pegs adopted by these nations as steps in the right direction. He suggests that the dollar standard in East Asia could be rationalized through collective action by national governments and considers the effect of American monetary and trade policies on the East Asian economy